MEKANISME TERJADINYA INFLAMASI DAN STRES OKSIDATIF PADA OBESITAS - rahmawati, ana (El-Hayah : Jurnal Biologi, 2014)
Obesity is a predisposing factor for metabolic syndrome that increases the risk of development of chronic diseases such as type 2 Diabetes Mellitus and atherosclerosis. Obesity is associated with a chronic inflammatory condition with progressive infiltration of immune cells in the adipose tissue of obesity. Adipose tissue is not only a triglyceride storage organ, but studies have shown the role of white adipose tissue as a producer of adipokines. Besides adipokines, also found several inflammatory mediators, such as interleukin-6 (IL-6). Adipokines have the function of regulating food intake, thus providing a direct effect on weight control. It is played by leptin, which is working on the limbic system by stimulating the uptake of dopamine, creating a feeling of fullness. But these adipokines induces production of reactive oxygen species (ROS), resulting in a process known as oxidative stress (OS). There are several mechanisms in producing the oxidative stress . The first is the oxidation of mitochondrial and peroxisomal fatty acid oxidation, which can generate ROS in the oxidation reaction, whereas other mechanisms is over-consumption of oxygen, which generates free radicals in the mitochondrial respiratory chain were found together with oxidative phosphorylation in the mitochondria. High fat diet also capable of generating ROS because it can alter the oxygen metabolism